Diagnostic markers of acute myocardial infarction - MYTHILI, SABESAN (Biomed Rep, 2015)
Acute myocardial infarction (AMI) is a major cause of morbidity and mortality worldwide. The highest risk of fatality occurs within the initial hours of onset of AMI. Thus, early diagnosis of cardiac ischemia is critical for the effective management of patients with AMI. Improper diagnosis of patients with chest pain often leads to inappropriate admission of patients without AMI and vice versa. In addition to clinical history, physical examination, accurate electrocardiogram findings and assessment of cardiac biomarkers have an important role in the early diagnosis of acute ischemia. The present review discusses in detail the various cardiac biomarkers released during the event of an AMI.